Burkina Faso : Basic Agricultural Public Expenditure Diagnostic Review (2004-2012) - World Bank (Washington, DC, 2015)
The rural sector, defined here as the economic sector that falls under the scope of the Ministry of Agriculture and Water (MAH), the Ministry of Animal Resources (MRA), and the Ministry of the Environment and Sustainable Development (MEDD), is one of the pillars of the Burkina Faso economy. Although its contribution to GDP has decreased in recent times from 35 percent in 1999 to 30 percent in 2011 due to the development of the other sectors of the economy, agricultural activity still employs approximately 86 percent of Burkina Faso s labor force and is the main source of income for poorer populations. Consequently, the rural sector is among the primary beneficiaries of public expenditures by the Burkina Faso government and constitutes one of the pillars of the Strategy for Accelerated Growth and Sustainable Development (SCADD) adopted in 2010. The goals of this agriculture public expenditure review in Burkina Faso are as follows: draw lessons from the past in terms of budget execution in the agricultural sector in order to promote the design and implementation of public expenditure programs that are more efficient and more equitable and have a greater impact; initiate the implementation of the databases and methodology required to conduct similar reviews regularly and thus contribute to the institutionalization of the process; and contribute to establishing the conditions for increased support for the sector while encouraging the harmonization and alignment of support with respect for national strategies.